El Cuarto Desnudo - Ibañez, Nuria (Mexico, 2013)
A look into the examination room of a children's hospital in Mexico City. Listening to the children, their parents and the doctors during consultations allows us to have a more profound and complex view of our social reality and of human nature.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films